2020
DOI: 10.1111/are.14504
|View full text |Cite
|
Sign up to set email alerts
|

Dietary lipid level and source affect metabolic responses in hybrid catfish (Pseudoplatystoma reticulatum × Leiarius marmoratus)

Abstract: This study was undertaken to evaluate the effect of dietary lipid source [linseed oil (LO, rich in 18:3 n−3); corn oil (CO, rich in 18:2 n−6); olive oil (OO, rich in 18:1n−9); and fish oil (FO, rich in LC‐PUFA)] and level (9% L and 18% L) on growth, body composition and selected plasma biochemistry parameters in hybrid catfish (Pseudoplatystoma reticulatum × Leiarius marmoratus) juveniles. Moreover, liver histology (lipids, glycogen, cell vacuolization) and key metabolic enzyme activities were also evaluated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…Lipid is essential nutrient for fish growth and development, which plays an important role in nutrition and physiology (Paulino et al., 2020; Xu et al., 2017, 2018). On the one hand, lipid acts as a form of energy storage and provides the body with metabolic energy to conserve dietary protein and limit ammonia production (Guo et al., 2019; Jiang et al., 2015; Wang, et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Lipid is essential nutrient for fish growth and development, which plays an important role in nutrition and physiology (Paulino et al., 2020; Xu et al., 2017, 2018). On the one hand, lipid acts as a form of energy storage and provides the body with metabolic energy to conserve dietary protein and limit ammonia production (Guo et al., 2019; Jiang et al., 2015; Wang, et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…According to Barroso et al., (2014) Z. morio has higher ratios of omega 6, saturated and monounsaturated fatty acids, as registered in the fatty acid analysis in the diets of our study. Further, it has been reported that fatty acid imbalance of n‐3/n‐6 could lead to lipid deposition of fish (Mu et al., 2018; Paulino et al., 2020). However, it is possible to modify the insect fatty acids profile manipulating the rearing substrate as reported by several authors (Belforti et al., 2016; Gasco et al., 2018; St‐Hilaire et al., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The fatty acid composition of the fish reflected dietary fatty acid composition. [ 31 ] On the other hand, n‐3 and n‐6 fatty acids share the same desaturatase, elongation enzyme, acetyltransferase, cycloxygenase, and lipoxygenase to produce eicosanoic acid series in fish. There is a metabolic competition inhibition between n‐3 and n‐6 fatty acids, and above enzymes have higher affinity for n‐3 PUFAs.…”
Section: Discussionmentioning
confidence: 99%